Jagten på den historiske Jesus - Mack, Burton L. (Religionsvidenskabeligt tidsskrift, 1996)
Burton L. Mack gives in this lecture an introduction to his work The Lost Gospel in which he points to the striking similarities between the historical Jesus and the cynic philosophers.